Shadow and extended shadow cost sharing associated to informal long-term care: The case of Spain - Raúl del Pozo-Rubio; Pablo Moya-Martínez; Marta Ortega-Ortega; Juan Oliva (Health Economics Review, 2020)
Background: A large part of the long-term care is provided by non-professional caregivers, generally without any monetary payment but a value economic of time invested. The economic relevance of informal caregivers has been recognized in Spain; however, public provision may still be scarce. The objective of this paper is to estimate the economic burden associated with informal long-term care that should assume the families through a new concept of cost sharing that consider opportunity costs of time provided by informal caregivers. Methods: The study sample includes all dependent adults in Spain. Socioeconomic information and the number of hours of informal care was collected through the Spanish Disability and Dependency Survey. The terms of shadow and extended shadow cost sharing were defined as the difference between the maximum potential amount of money that families could receive for the provision of informal care and the amount that actually they received and the value of informal care time with respect to the amount received, respectively. Results: 53.87% of dependent persons received an economic benefit associated to informal care. The average weekly hours of care were 71.59 (92.62 without time restrictions). Shadow cost sharing amounted to, on average, two thirds, whereas the State financed the remaining third. In terms of extended shadow cost sharing, the State financed between 3% and 10% of informal care provided by caregivers. Conclusions: This study reveals the deficient support received for the provision of informal care in Spain. More than 90% of informal care time is not covered by the economic benefits that families receive from the State.
Keywords: D63; I38; J14; 330; Informal care; Economic value; Long-term care; Spain